Determinants of Tax Avoidance: The Role of Corporate Social Responsibility and Managerial Ownership in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) During 2020–2024 - Fastabiqul Khoiroh; Achmad Wicaksono; Chairil Anwar; Erlyna Tri Rohmiatun (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Tax avoidance remains a major issue in Indonesia’s manufacturing sector despite the implementation of tax reform policies through the Harmonization of Tax Regulations Law. Corporate Social Responsibility (CSR) and managerial ownership are frequently associated with corporate decisions related to tax compliance; however, previous studies have reported inconsistent findings regarding their influence on tax avoidance. Using a quantitative associative approach, data were collected from annual and sustainability reports of food and beverage manufacturing companies listed on the Indonesia Stock Exchange during 2020–2024. The sample was selected through purposive sampling, resulting in 210 observations. Data analysis employed descriptive statistics, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination analysis. The findings indicate that CSR has a positive and significant effect on tax avoidance, suggesting that broader CSR disclosure may coexist with corporate tax efficiency strategies. Meanwhile, managerial ownership does not significantly affect tax avoidance. Simultaneously, CSR and managerial ownership also fail to significantly explain variations in tax avoidance behavior. The low explanatory power of the model indicates that tax avoidance practices are influenced by more complex external factors, including fiscal regulation, industry conditions, and corporate tax policies. These findings contribute to the literature on corporate governance and taxation in the post-tax reform era in Indonesia.